Influence of Initial Surface Roughness on LIPSS Formation and Its Consecutive Impact on Cell/Bacteria Attachment for TiAl6V4 Surfaces - Sotelo, Lamborghini; Fontanot, Tommaso; Vig, Sanjana; Herre, Patrick; Yousefi, Peyman; Fernandes, Maria Helena; Sarau, George; Leuchs, Gerd; Christiansen, Silke (Advanced Materials Technologies, 2023)
The influence of the initial surface roughness of TiAl6V4 samples on the orientation and periodicity of the resulting laser-induced periodic surface structures (LIPSS), as well as the surface wettability and chemistry is reported here. Before LIPSS fabrication, initial sample surface roughness is adjusted by variations of finial polishing steps with polishing grain sizes of 18.3, 8.4, 5, and 0.5 µm. A 3 × 3 irradiation matrix was defined and lasered on all samples by changing the laser power and distance between consecutive laser scans. The resulting structures were characterized by scanning electron microscopy (SEM), atomic force microscopy, Raman spectroscopy, and contact angle measurements. As a further step, three representative generated structures were chosen to explore their bone implant viability by resazurin assays, alkaline phosphatase activity, and direct SEM imaging of the induced cells (MG63) and bacteria (Escherichia coli and Staphylococcus aureus). Results show that initial surface roughness has big influence on the wettability of the resulting surface, as well as inducing small variations on the orientation of the generated LIPSS. Structures generated with a higher integrated fluence have also shown to enhance cell differentiation while reducing bacterial activity, making them a great candidate for improved bone implant compatibility and durability.
CRIS-Team Scopus Importer:2023-04-20
Keywords: biocompatibility; laser functionalization; laser-induced periodic surface structures; TiAl6V4